Step-by-step explanation:
Hey there!
0.3 = 3/8 (equal to eachother)
Reason: (<u>3</u><u>/</u><u>8</u><u> </u><u>=</u><u> </u><u>0.375</u><u>)</u>
<u>So</u><u>,</u><u> </u><u>0</u><u>.</u><u>3</u><u> </u><u>is</u><u> </u><u>equal</u><u> </u><u>to</u><u> </u><u>eachother</u><u>. </u>
<u>0</u><u>.</u><u>3</u><u>=</u><u>0</u><u>.</u><u>3</u>
<em><u>Hope it helps</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em>
<span>Find the inverse of the given function.
f(x) = -1/2√x + 3, x ≥ -3
I will have to assume that you meant f(x) = -(1/2)sqrt(x) + 3. If you actually meant f(x) = -(1/2)sqrt(x+3), then obviously the correct result would be different.
1. Replace "f(x)" by "y:" y </span>= -(1/2)sqrt(x) + 3
2. Interchange x and y: x = -(1/2)sqrt(y) + 3
3. Solve for y: x-3=-(1/2)sqrt(y), so that 2(3-x)= sqrt(y) and y=+sqrt(2[3-x])
4. Replace "y" with
-1
f (x) = sqrt(2[3-x])
Here, there are restrictions on x, since the domain of the sqrt function does not include - numbers. The domain here is (-infinity,3]
4 times 4=16 So in four days, Cheyrl traveled 16 miles.